2007
DOI: 10.1128/jvi.00016-07
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus Infection Promotes Invasion of Primary Human Umbilical Vein Endothelial Cells by Inducing Matrix Metalloproteinases

Abstract: Matrix metalloproteinases (MMPs) play important roles in cancer invasion, angiogenesis, and inflammatory infiltration. Kaposi's sarcoma is a highly disseminated angiogenic tumor of proliferative endothelial cells linked to infection by Kaposi's sarcoma-associated herpesvirus (KSHV). In this study, we showed that KSHV infection increased the invasiveness of primary human umbilical vein endothelial cells (HUVEC) in a Matrigelbased cell invasion assay. KSHV-induced cell invasion was abolished by an inhibitor of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 52 publications
3
91
1
Order By: Relevance
“…In the following experiments, we focused our efforts on the early stage of KSHV infection. stage of KSHV infection (27,57,81,84). While some proinflammatory and proangiogenic cytokines have been shown to regulate endothelial permeability in some pathological conditions (21,33,34,47,65), confluent endothelial cells are usually refractory to these cytokines partly because of the growth contact-inhibition effect exerted by the adherens junctions (13,37,46,64).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following experiments, we focused our efforts on the early stage of KSHV infection. stage of KSHV infection (27,57,81,84). While some proinflammatory and proangiogenic cytokines have been shown to regulate endothelial permeability in some pathological conditions (21,33,34,47,65), confluent endothelial cells are usually refractory to these cytokines partly because of the growth contact-inhibition effect exerted by the adherens junctions (13,37,46,64).…”
Section: Resultsmentioning
confidence: 99%
“…The disruption of adherens junctions mitigates contact inhibition and facilitates the growth of endothelial cells by transmitting mitogenic and survival signals, such as Src, phosphatidylinositol 3-kinase (PI 3-kinase), proteinase kinase C, protein kinase B, and mitogen-activated protein kinases (MAPKs), activated by extracellular growth and proangiogenic factors and by releasing ␤-catenin to the nucleus to promote the transcription of oncogenes, such as c-myc and cyclin D1 (15,71,74). We and others have shown that KSHV infection of endothelial cells activates many of these pathways and promotes the growth, angiogenesis, and invasion of the infected cells while simultaneously inducing proinflammatory and proangiogenic cytokines (14,27,54,57,66,67,76,81,82,84), which are consistent with the observed phenotypes of disruption of adherens junctions and increased endothelial permeability described in this study. Interestingly, these features are also characteristics of cellular transformation and the epithelial-to-mesenchymal transition of cancer cells (6,39).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 After infection, KSHV stimulates EC invasiveness by inducing extracellular matrix metalloproteinases (MMPs) such as MMP-1, MMP-2, and MMP-9. 10 Because the majority of cells in KS lesions and in KSHV-infected ECs are latently infected by KSHV, 4 viral latent proteins may, at least in part, contribute to the invasiveness of KSHV-infected cells. We have shown recently that K15M is a KSHV latent protein capable of inducing cell migration and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 To identify the mechanisms involved, we analyzed KSHV-regulated genes in infected ECs. We used a recombinant KSHV expressing GFP 20 to infect a pure population of LECs.…”
Section: Kshv Introduces Tumor Traits and Migration Potential Into Lymentioning
confidence: 99%
“…In KS tumor cells, KSHV is predominantly in the latent state, and latent KSHV infection of endothelial cells can promote angiogenesis-related phenotypes, including increased tubule stability of macrovascular endothelial cells, induction of angiogenesis and capillary morphogenesis under low-growth-factor conditions, and enhanced migration and invasion (12)(13)(14)(15)(16)(17). During latent infection, KSHV expresses 6 genes, latency-associated nuclear antigen (LANA), vCyclin, vFLIP, and kaposins A, B, and C. Additionally, KSHV encodes a number of microRNAs (miRNAs) during latent infection.…”
mentioning
confidence: 99%